Is causation deterministic or probabilistic? A critique of Frosch and Johnson-Laird (2011). Issue 8 (17th November 2021) - Yin, Pengfei; Sun, Jinrui
ABSTRACT: The mental model view of causation is deterministic, which claims that " A causes B means that given A, the occurrence of B is necessary" (Johnson-Laird et al., 2017). Frosch and Johnson-Laird [2011). Is everyday causation deterministic or probabilistic? Acta Psychologica, 137, 280–291. https://doi.org/10.1016/j.actpsy.2011.01.015] provide an empirical study to support this proposal. Several facets of causal pluralism established in previous works motivate us to suspect the monistic determinism. Therefore, we analyse Frosch et al.'s experimental issues from logical and methodological perspectives, such as the hidden circular argument, the insufficient and unnecessary condition of their tasks as the criterion of determinism and the biases toward deterministic reading through several hints. Our redesigned experiments from three perspectives—concept, judgment, and inference—coherently demonstrate that people have a pluralistic rather than a monistic perspective of the modal conception of causation. We account for modal pluralism from two perspectives. Several theoretical and methodological relationships with prior work are also discussed.